2015
DOI: 10.1007/s12663-015-0810-5
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Canine Retraction by Distraction of the Periodontal Ligament and Dentoalveolar Distraction Methods

Abstract: No significant differences in the various parameters were found between both the techniques of canine retraction by distraction osteogenesis, while reducing orthodontic treatment duration by 6-9 months without any unfavorable short-term effects on the periodontium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…In the PDLD groups, OTM and periodontal regeneration were both significantly enhanced compared with the control, which is consistent with previous study findings on PDLD 6–8 . To date, in vivo studies on PDLD have primarily used a frequency of two times/day 7,9,20 . In the present study, a higher stretch frequency (six times/day, a fairly high frequency allowed by manually applying force to a dog since there were no automatic distraction devices available) was attempted, and the effects of the two different stretch frequencies on OTM and bone remodelling were compared under the same daily stretch conditions.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the PDLD groups, OTM and periodontal regeneration were both significantly enhanced compared with the control, which is consistent with previous study findings on PDLD 6–8 . To date, in vivo studies on PDLD have primarily used a frequency of two times/day 7,9,20 . In the present study, a higher stretch frequency (six times/day, a fairly high frequency allowed by manually applying force to a dog since there were no automatic distraction devices available) was attempted, and the effects of the two different stretch frequencies on OTM and bone remodelling were compared under the same daily stretch conditions.…”
Section: Discussionsupporting
confidence: 86%
“…[6][7][8] To date, in vivo studies on PDLD have primarily used a frequency of two times/day. 7,9,20 In the present study, a higher stretch frequency (six times/day, a fairly high frequency allowed by manually applying force to a dog since there were no automatic distraction devices available) was OTM and bone remodelling were compared under the same daily stretch conditions. We found that greater expression of mature COL-I and OCN were observed in the six times/day-PDLD group than in the two times/ day-PDLD group, which indicated that at higher distraction frequency, the synthesis of periodontium on the tension side was more active.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“… 1 - 3 One of the common deterrents to orthodontic therapy is the amount of time in which a patient needs to commit, thus, there has been a continuous search for techniques to accelerate the rate of orthodontic tooth movement. 4 At present, there are various invasive techniques to accelerate the rate of orthodontic tooth movement, namely: surgically facilitated orthodontics; 5 combination of interradicular corticotomy and supra-apical osteotomy technique; 6 , 7 periodontal ligament distraction; 8 undermining of interseptal bone; 9 the corticotomy-facilitated technique; 10 dentoalveolar distraction osteogenesis; 11 micro-osteoperforation, 12 and piezopuncturing. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the clinical effects of PDLD require further observation. [21]. The external force applied to orthodontic teeth is transmitted to the peripheral bone of the bone segment through the periodontal ligament, which in turn causes differentiation of osteoblast and osteoclast in the periodontal tissue.…”
Section: (B) Piezocisionmentioning
confidence: 99%